Analisis Rancangan Tata Letak Fasilitas Toko Roti A Dengan Pendekatan Activity Relationship Chart (ARC), Total Closeness Rating (TCR) Dan Ongkos Material Handling (OMH) - Tiara; Perdana, Surya; Atikah (BULLET : Jurnal Multidisiplin Ilmu, 2024)
A's Bakery has an inadequate facility layout, which reduces productivity and service quality. To improve operational efficiency and enhance movement efficiency in the store, the facility layout must be reorganized. All areas and spaces in A Bakery, including the display, cashier, kitchen, toilet, storage, and dining area, are included in the primary data of this research. This research uses the Activity Relationship Scheme (ARC) and Total Closeness Rating (TCR) for data processing. The results of the Total Closeness Rating (TCR) calculation show the order of development priorities, with TCR values of 192 for the display area, 110 for the kitchen, 110 for the cashier, 97 for the dining area, 92 for the warehouse, and 6 for the restroom. Based on distance calculations and material handling costs, it was found that the initial distance results decreased from 1,398.00 to 840.1 and the material handling cost calculation results decreased from 2,255,742.91 to 1,355,543.37, this can make bakery A effective and efficient based on the layout of existing facilities. The result of this calculation forms a layout solution, which includes block templates, suggested alternative layouts, and optimal layouts.